The haunted house next door - Miedoso, Andres (Miedoso, Andres. Desmond Cole ghost patrol, 2017)
When supernatural things start happening in the house timid Andres and his parents just moved into, next-door-neighbor Desmond Cole, eight, comes to the rescue.